A Parsimonious Instrument for Predicting Students' Intent to Pursue a Sales Career: Scale Development and Validation. (April 2014) - Peltier, James W.; Cummins, Shannon; Pomirleanu, Nadia; Cross, James; Simon, Rob
Students' desire and intention to pursue a career in sales continue to lag behind industry demand for sales professionals. This article develops and validates a reliable and parsimonious scale for measuring and predicting student intention to pursue a selling career. The instrument advances previous scales in three ways. The instrument is generalizable across academic settings and is shown to be sensitive to differences across varied course coverage and learning activities. The instrument is parsimonious and offers a high reliability coefficient. Finally, the instrument is validated both before and after exposure to a sales module, thus capturing perceptual and attitudinal changes as students become more familiar with this career option.